Re-description of Medetera glaucella Kowarz, 1878 (Diptera, Dolichopodidae) based on type material - Naglis, Stefan; Negrobov, Oleg P. (Zootaxa, 2014)
In his monograph of the genus Medetera, Kowarz (1878) described Medeterus glaucellus based on specimens from Italy and Austria collected by Mik, and from Romania collected by himself. He noted the resemblance to M. muralis Meigen, 1824, since both species lack dorsal setae on the mid tibia, and distinguished his new species by the white lower postocular setae and the white setae on the propleura and coxae. In the revision of the Palaearctic Medeterinae (Negrobov & Stackelberg 1971–77) the re-description of M. glaucella was not based on type specimens and the male hypopygium was not examined and figured. We have examined syntypes of M. glaucella from the Kowarz collection of the Naturhistorisches Museum Wien and have designated a lectotype in order to preserve stability of nomenclature. In addition, we give a re-description of M. glaucella based on the type material and provide figures of the male hypopygium for the first time.